The Impact of Individual and Organizational Reputation on Physicians' Appointments Online. Issue 4 (1st October 2016) - Liu, Xiaoxiao; Guo, Xitong; Wu, Hong; Wu, Tianshi
ABSTRACT: Insufficient research exists on the impact of reputation in online health-care market communities, especially from the multilevel and cross-level perspectives. Based on prior research on individual and organizational reputation, we hypothesize multilevel and cross-level reputation determinants of physicians' performance in online health-care market communities. Using hierarchical linear modeling, we analyzed the data of 47, 182 physicians from 660 hospitals in a Chinese online health-care market community to test our hypotheses. Our results suggest that the number of physicians' appointments is positively associated with their individual offline and online reputations, as well as the offline and online reputation of the hospital in which the physicians work. We also find that organizational reputation moderates the relationship between an individual's reputation and a physician's performance, in such a way that the hospital's offline reputation increases the importance of physicians' online reputation in promoting the number of physicians' appointments. However, the hospital's online reputation enhances the relationship between physicians' offline reputation and the number of appointments. Our study contributes to existing theories of reputation and the signaling theory, and also provides physicians with guidelines that support them in effectively improving their performance.